Conceptualizing Nation in the Glass of Canada’s Crystal Palaces - Weber, Stephanie (Material Culture Review / Revue de la culture matérielle, 2023)
This paper attempts to define a visual culture of plate glass in Canadian exhibition buildings during the second half of the nineteenth century. I approach this material through descriptions and depictions in Canadian periodicals vernacular versions of the “Crystal Palace” exhibition building. In Canadian publications, their glass surfaces often take on certain metaphorical significance, coming to stand in for modernity, to signify purity by their clarity, or to promise a quintessentially modern honesty and openness, as their solid surfaces maintained visual limpidity. However, though glass is allusive in many ways, its signification also remained elusive. Any meaning that glass may encompass is always accompanied by its own opposite; glass can change in a moment from lucid to reflective, from refracting beams of bright light to darkening and dulling, and though it is a physically protective layer, it also permits unmitigated visual connection. The relationship of nineteenth-century Canadian periodicals to the material is marked by this ambiguity. I suggest that glass’s physical capacity for dualism is an apt metaphor for the way that the meanings it signified were often contradictory, even when simultaneous. I argue that in the context of these buildings, which intended to put the industry of Canada on display in the service of defining and asserting an emerging nationalism, the paradoxes encompassed by the developing cultural imaginaries around glass are mirrored by the paradoxes of Victorian Canadians’ ambiguous and conflicting relationships with nationalism and modernization.